Reliability Study of Oil and Gas Pipelines Using the Normal Distribution Method - Suhendi Syafei, Nendi; Hidayat, Darmawan; Rohadi, Nanang; Joebaedi, Khafsah; Supriyana, Eddy (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Gas and oil pipelines have decreased function and damaged due to corrosion. This research aims to analyze and predict the life of gas and oil pipelines within a certain time span. The method used is a reliability study using a normal distribution. The analysis results show it is predicted that the pipe reliability probability in 2030 will decrease and the probability of failure will increase. The probability of reliability is 0.843572786617270 and the probability of failure is 0.156427213382730 in 2030. With the long distance pipeline, maximum depth as shown in the attachment the average thick remain is 0.2200 inches, the average corrotion rate is 0.0317 mm/year, with prediction thick remain from 2000 to 2030 in inches.